A statistical quality control study on Magiclean Corporation - Casinto, Gerly D.; Tamayao, Mili-Ann M.; Velasco, Vida Gracia B. (Diliman, Quezon City College of Engineering, 2007)
Magiclean Corporation is a developing company which has a product line that includes a wide range of household products. Fifty percent of total sales is attributed to its two top selling-products namely dishwashing Liquid-Lemon Scent and Fabric Softener Twist. As suggested by the company, the research focused on these two. Specifically, the group focused on their pH and viscosity, two factors which were identified as most critical by the company. It was desired to switch from a 2-sigma to a 3-sigma control limit for these factors, or the purpose of sampling reduction (per batch). It has been proven that the 2-sigma control charts are not suitable for pH and viscosity testing, since too many plotted points have been observed out of control. Control charts using 3-sigma control limits have been made and show that there are discrepancies between the two types of charts. However, the 3-sigma control limits is alarmingly out of control. This has been attributed to an unacceptably high variability which results in more than 100% use of specification band. The unfavorable condition may be also be because the process mean has shifted to distributing, new, out-of specification mean. It is therefore recommended that a critical review of the processes and the product design be conducted. This will lead to a better understanding of why these failures occur. FMEA diagram for the process design was constructed by the group to give the company a headstart on which factors to study. Through this, it was found out that the most critical processes in the production of the Dishwashing Liquids are Preparation of Raw Materials, Neutralization and Addition of Minor Ingredients. On the other hand, the critical aspects for the Fabric Softener are the preparation of Raw Materials, Settling/Cooling Down and Addition of Viscosity Modifier and Biocides.
In preparation of raw materials, problem occurs when there is discrepancy between the amount of raw materials withdrawn and the raw materials used in the manufactured product. Unacceptable discrepancy could amount to P66,000 opportunity cost on sales per lot of product put on hold. To address this problem, the group recommends that the company establish a systemic and strictly implemented procedure in the preparation of raw materials, as well as proper training of the operators. In addition, a rectifying inspection program at the early stage of production process should be formulated and implemented. The group suggests that a Continuous Sampling Plan-1 (CSP-1) is most suitable. In further studies regarding the achievement of the target mean, it is suggested that a Design of Experiments be performed. A propose structure of this has been provided by the researchers. For the control limits for the in-control process, it is recommended that 2-sigma limit be implemented initially until process is indeed producing good quality. With a high probability of acceptance, a switch to 3-sigma limits can be done. Finally for the sampling frequency, a continuous sampling is suggested since the Dishwashing Liquid and Fabric Softener do not result in a natural formation of lots. However at the moment, the group does not advise a reduction in sampling frequency of the in-process inspection of pH level and viscosity of both products. 100% inspection should be continued as well as carrying out the proposed Design of Experiment, and focus on eliminating the possible causes of failures shown in the FMEA. Only after the process is already proven in-control can the company proceed to lessening the sampling frequency.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Magiclean Corporation; Dishwashing liquids; Quality control